The dimensions of efficiency and effectiveness of clinical directors in Western Australia's public teaching hospitals - Dedman, Graeme Lee (Curtin University, 2008)
The management of healthcare has changed dramatically over the past two decades. Such change has not just been in the way medicine is practiced, but also in the way the health dollar is spent. Hospitals have found themselves under constant and increasing pressure to not only reduce costs in relative terms, but also at the same time, provide new and expanded services. These pressures caused hospitals worldwide to closely examine the means by which they met the demands that were placed upon them (Royal Perth Hospital, 1994a; Asay and Maciariello, 1991). One common response was to embrace New Public Management strategies, such as devolved management. That is, to place the responsibility for managing diminishing health care resources, into the hands of those who use them the most - doctors (Chantler, 1993). To achieve this many hospitals adopted organisational structures known as clinical directorates (Chantler, 1993). Following international trends, the clinical directorate model was adopted by all of Western Australia’s public teaching hospitals in the mid 1990s. The belief was that by devolving hospital management to doctors, the clinical knowledge they possess will lead to improved clinical outcomes through the better allocation of resources. From the perceptions of Clinical Directors, Chief Executives, Nurse Managers, Business Managers and Department Heads, this research has developed a model, termed the Clinical Director Efficiency and Effectiveness (CD2E) model, that describes the dimensions of efficiency and effectiveness of Clinical Directors in the Western Australian public teaching hospital context.The model proposes that there are three perceived dimensions of efficient and effective clinical directorship. They are: those that are brought to the role by doctors and governed by the health environment in which they develop (Domain Knowledge and Skills), those that are learned (Business Skills) and those that are innate (Personal Attributes). The three perceived dimensions consist of nine components. ‘Domain Knowledge and Skills’ comprise clinical expertise, peer influence, political expertise and environment knowledge. ‘Business Skills’ comprise financial management, strategic management and human resource management. ‘Personal Attributes’ comprise commitment and participation, and communication. The CD2E model not only describes the perceived dimensions of efficiency and effectiveness, it also outlines those dimensions that are brought to the role of a Clinical Director by the medical profession and those areas where there are perceived deficiencies. Whilst the final CD2E model can be used to assist in developing and selecting future Clinical Directors who are more appropriately equipped to improve healthcare delivery within Western Australia, the literature suggests that the model also has features which are common and applicable to other health environments.